PENGARUH PEMBERIAN MINYAK ESENSIAL LAVENDER TERHADAP KEJADIAN NYERI DAN INFEKSI PASCA PERSALINAN DENGAN EPISIOTOMI DI RSUD PANEMBAHAN SENOPATI BANTUL - , wahyuningsih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Episiotomy is a surgical procedure that leads to problems for those who are post childbearing. The problems are commonly pain and perinea infection. Applying essential lavender oils is one of a complementary intervention that can alleviate that problem. Research Objectives: This study aims to examine effects of essential lavender oils on arising pain and infection for childbirth mothers with episiotomy procedure. Research Methodology: This Quasi Experiment study used Nonequivalent Control Group design and Consecutive Sampling Technique. Episiotomy was assessed using REEDA (Redness, Edema, Ecchymosis, Discharge, Approximately) and pain measurement was using NRS (Numeric Rating Scale). Research tool was French 40/42 type essential lavender oils with 0,04% dilution. Lavender essential oils were applied topical. Data was analyzed using Chi-Square and Fisher Exact. Finding: Statistically, application of lavender essential oils in second days given significant impact on pain with RR: 0,11 (95% CI: 0,03-0,35), p-value=0.00. Whereas, application the oil for infection was statically giving distinct result on first day and on days two with RR:0,12 (95% CI:0,04-0,37), p-value=0.00, and RR:0,10 (95% CI:0,03-0,42), p-value=0.00 respectively. Conclusion: Application essential lavender oils for case group was effective for pain in second day. Essential lavender oils were also